Discussing Migraine With Your Patients : A Common Sense Guide for Clinicians - Marcus, Dawn A.; Ready, Duren Michael (Springer New York : Imprint: Springer, 2017)
This engaging and highly practical title is designed to support healthcare professionals in providing the best possible care for their patients with migraine. Developed by two leading authorities in the field who bring wit and warmth to their writing, the book combines the valuable wisdom of their clinical expertise with cutting edge scientific synthesis and helpful clinical pearls. Replete with a plethora of instructional aids and clinical tools (such as patient handouts, questionnaires, checklists, video clips, and quick-reference boxes), Discussing Migraine with Your Patients: A Common Sense Guide for Clinicians reviews migraine treatment in an evidence-based manner -- according to the empirical data and FDA and consensus-based guidelines. Discussion topics include acute and preventive pharmacotherapy, medical interventions and devices, behavioral and psychological nonpharmacologic therapies, education, trigger management, healthy lifestyle practices, stress management, neutraceuticals, and alternative medicine offerings. In addition, this easy-to-read title covers genetics and pathophysiology, symptoms and comorbidities, and a range of essential clinical skills that are useful in achieving the best possible outcomes with patients. In invaluable addition to the literature, this title will serve as the ultimate go-to resource for primary care clinicians and trainees. Headache specialists, too, will find value in this work.- Resumé vydavatel
Keywords: vnitřní lékařství; urgentní medicína; neurologie; primární péče; migréna; internal medicine; emergency medicine; neurology; primary care; migraine; elektronické knihy; monografie; electronic books; monography